Pertanggungjawaban Pidana Pemalsuan Merek Dalam Hukum Positif Indonesia dan Hukum Islam - Mawaddah, Fithri; Haikal, Mohammad; Saputra, Fedri; Akbar, Khairil; Efendi, Sumardi (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2023)
Brand counterfeiting is very disturbing to the public as consumers who always use the brand image of certain products, but the perpetrators of brand counterfeiting continue to increase, therefore they need to be held criminally responsible for their actions. With a legal normative approach, namely by considering laws and norms and concepts related to the boundaries of legal units so that the sanctions obtained as a form of legal responsibility for the perpetrators of counterfeiting this article try to find the answer, so that in the end a conclusion is obtained in Indonesian positive law that the sanctions are regulated in the Law of the Republic of Indonesia Number 20 of 2016 concerning Marks and Geographical Indications with a maximum sanction of 5 (five) years and/or a maximum fine of Rp. zir which is returned to the authorities/judges in imposing sanctions that can provide a sense of justice for all.